Azadirachtin exposure inhibit ovary development of Spodoptera litura (Lepidoptera: Noctuidae) by altering lipids metabolism event and inhibiting insulin signaling pathways - Ranran Sun; Liwei Jiang; Wenlong Chen; Yuanhao Xu; Xin Yi; Guohua Zhong (Ecotoxicology and Environmental Safety, 2023)
Lipids are main energy source for insects reproduction, which are becoming emerging target for pest management. Azadirachtin (AZA) is a multi-targeted and promising botanical insecticide, but its reproduction toxicity mechanism related to lipids metabolism is poorly understood. Here, we applied lipidomic and transcriptomic to provide a comprehensive resource for describing the effect of AZA on lipids remodeling in ovary of Spodoptera litura. The results showed that AZA exposure obviously altered the contents of 130 lipids subclasses (76 upregulated and 54 downregulated). In detail, AZA exposure changed the length and saturation degrees of fatty acyl chain of most glycerolipid, phospholipid and sphingolipid as well as the expression of genes related to biosynthesis of unsaturated fatty acids and fatty acids elongation. Besides, following the abnormal lipids metabolism, western blot analysis suggested that AZA induce insulin resistance-like phenotypes by inhibiting insulin receptor substrates (IRS) /PI3K/AKT pathway, which might be responsible for the ovary abnormalities of S. litura. Collectively, our study provided insights into the lipids metabolism event in S. litura underlying AZA exposure, these key metabolites and genes identified in this study would also provide important reference for pest control in future.